Germplasm storage at ILCA - Hanson, Jean; Ruredzo, T.J. (Australian Centre for International Agricultural Research, 1990)
Looks into ILCA'S genebank which has a collection of over 9000 accessions of forage germplasm of grasses, legumes and browse. The majority of accessions are stored by conventional methods of seed storage confirming to international standards as far as possible. However, there are some species of grasses which rarely produce seeds and which are currently stored in a field genebank. In vitro techniques are being developed for the management of these and some browse species, which take a long time to produce seeds. The methods used and the germplasm stored are described.